The Seven habits of highly effective people [soundrecording] - Covey, Stephen R.; Perrin, Susan (New York Simon & Schuster, 1989)
Discusses habits, i.e. personal vision, leadership habit, personal managements, synergy, etc., that people should adopt to live an effective life. Sets a paradigm for individuals.
Keywords: Success -- Psychological aspects; Character; Meditation; Self-actualization (Psychology); Personality development; Psychology; Public administration